Transferências intergovernamentais e estrutura fiscal: estudo dos pequenos municípios do estado de Minas Gerais (2014- 2022) - Maia, Renata Cristina Pereira (2024)
The 1988 Federal Constitution gave municipalities political and tax autonomy, recognized these local governments as members of the federation and instituted the distribution of resources through intergovernmental transfers, thus favoring small businesses. Despite the autonomous recognition and the increase in revenue available to municipalities, the picture of the vast majority of municipalities created based on this rule is of a low population size, of less than 10,000 inhabitants, without consistent economic activity, which provides them with conditions of fiscal self-sufficiency and tax and low technical capacity in municipal management. The great dependence on intergovernmental transfers is also highlighted, given that its own revenue is generally insufficient and with expenses exceeding the executive and legislative costs, making development difficult. Based on this discussion, the present work seeks to analyze the fiscal structure and the degree of financial dependence of small municipalities in the State of Minas Gerais, from 2014 to 2022. The methodology is characterized as descriptive, quantitative research, with a comparative analytical approach, which will provide descriptive analyzes of the behavior of intergovernmental transfers and the own tax collection of small municipalities in the State of Minas Gerais throughout the period studied. This study showed that there is a high degree of dependence on transfers from other spheres of government to make up the total revenue that the 482 municipalities had available during the period 2014-2022, which reached an average of 83%. Likewise, the own collection effort is too low in these municipalities, which was, on average, 4.4%, which points to the reduced use of the collection capacity. Finally, this study offers practical guidance for municipal managers to increase the collection of municipal taxes.